Nile conflict: Compensation rather than mediation. How Europeans can lead an alternative way forward - Tobias von Lossow; Luca Miehe; Stephan Roll (Stiftung Wissenschaft und Politik (SWP), 2020)
The conflict between Egypt and Ethiopia over the distribution and use of the Nile water has entered a new phase. Questions about how and over what period of time the reservoir of the Grand Ethiopian Renaissance Dam (GERD) will be filled are taking centre stage. Against this backdrop, the USA launched a new mediation attempt at the end of 2019. However, initial hopes of a swift agreement have not materialized. The longer substantial results are postponed, the more apparent it becomes that external mediation alone will not suffice to resolve the dispute. In order to defuse the conflict, it might be necessary for Egypt to compensate Ethiopia for concessions on the GERD. Germany and its European partners should provide Egypt with financial support for creating a compensation mechanism. This would promote stability in Europe's conflict-ridden neighbouring region, and reduce migration pressure. But Europeans should tie financial contributions to clear conditions vis-à-vis Cairo, aimed at improving water management and overall governance.
Keywords: 320